Fear and Practice Modifications of Dentists During the Omicron ERA of Covid-19 - Fahad Ismail, Muhammad Usman Muneer, Junaid Altaf, Nadia Munir, Sajjad Ali Darvesh, Muhammad Zeeshan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background/Aim: After the rapid spread of the COVID 19 when it first started in December 2019, the omicron wave of the infection started to rise again in November 2021. During this time Centers for Disease Control and Prevention came up with a comprehensive plan in place which allowed dentists to treat patients safely. Due to the fear of contraction of the virus and its easy transmissibility, it begs to reason that dental practitioners should modify the clinical practice to ensure optimal cross infection control. Methods: Our sample size consisted of 290 respondents from all over Pakistan, all of whom were dental practitioners using a standardized questionnaire. The data were analyzed using SPSS V.23. Frequencies were calculated & the Mann-Whitney u-test of significance was applied to the responses. Results: It was seen that out of the 290 respondents, 79% of the total respondents were anxious about treating patients with suspicious signs and symptoms of COVID-19 and 81% of the respondents were afraid of carrying the infection back to their families. On the other hand, only 49% of the respondents said that they use N95 respirators while treating patients, 28% of the respondents said that they were using rubber dams for aerosol-generating procedures and 49% said that they would perform 4 to 6 handed dentistry. Conclusion: There was a lack of adherence to the CDC proposed guidelines by the majority of the respondents despite having fear regarding the transmissibility of the disease.